PENGARUH PEMBIAYAAN BERMASALAH DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS BTPN SYARIAH PERIODE 2015-2020 - Itsnaini Chusnul Khotimah; Nadiyah Susilawati (Program Studi Ekonomi Syariah, 2022)
The problem faced by Islamic banking to date is the problem of financing in Islamic banking itself. This problematic financing is then related to the bank's profitability in assessing its health. The financing problems faced by banks need to make the bank implement several strategies to improve Non Performing Financing (NPF), namely rescheling (rescheduling), reconditioning (reconditioning), restructuring (rearrangement) and foreclosure of collateral. If a bank is able to generate profits effectively and efficiently, maximum profitability can be achieved. Profitability as a basis to see the company's ability to earn a profit within a certain period. The ability of a company to earn a profit will attract investors to invest in the company so that the company can expand its business. BTPN Syariah As the only sharia commercial bank in Indonesia that focuses on providing services for empowering productive underprivileged customers and developing inclusive finance, BTPN Syariah also provides access to public finances and provides simple financial training to help the community's livelihood with its empowerment program. This study aims to determine whether non-performing financing and operational efficiency have an impact on the profitability of BTPN Syariah using descriptive quantitative methods.